Last duel - Scott, Ridley; Holofcener, Nicole; Affleck, Ben, 1972-; Damon, Matt; Walsh, Kevin J., 1975-; Fox, Jennifer; Driver, Adam; Comer, Jodie, 1993-; Walter, Harriet; Ivanek, Zeljko, 1957-; Csokas, Marton, 1966-; Lawther, Alex, 1995-; et al. (Los Angeles, California 20th Century Studios, 2021)
After the wife of knight Jean de Carrouge accuses his squire of assaulting her virtue, King Charles VI declares that the men must fight to the death, leaving the truth to be revealed by God who will let the guilty man perish. This arrangement will leave the woman either berieved or besmirched, her life and position in society ruined no matter the result.
Widescreen.
Title from disc surface.
Originally released as a motion picture in 2021.
Based upon the book "The last duel: a true story of trial by combat in medieval France" by Eric Jager.
Director of photography, Dariusz Wolski ; editor, Claire Simpson ; music, Harry Gregson-Williams.
Matt Damon, Adam Driver, Jodie Comer, Harriet Walter, Zeljko Ivanek, Marton Csokas, Alex Lawther, Ben Affleck.
Keywords: To 1515; Kings and rulers -- 14th century -- Drama; Dueling -- France -- 14th century -- Drama; Scandals -- France -- History -- To 1500 -- Drama; Wager of battle -- France -- History -- To 1500 -- Drama; Rape -- 14th century -- Drama; France -- History -- Medieval period, 987-1515 -- Drama; France -- History -- 14th century -- Drama; DVDs; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; History; Film adaptations; Fiction films; Epic films; Drama; Historical films